Nutmeg (Myristica fragrans) Of North Minahasa Molecular Entication Based on chloroplast DNA of matK gene - Fanny Nella Nanlohy; Yermia Semuel Mokosuli (Indonesian Biodiversity Journal, 2020)
Plant Nutmeg (Myristica fragrans) is an endemic plant in Indonesia originating from Banda Maluku Province. Nutmegs have long been known to people as spices. The nutmeg plants have been cultivated in North Sulawesi for a long time. This research has been conducted to obtain the position of species and the reconstruction of the phylogenetic tree of nutmeg plant (Myristica fragrans) from North Minahasa based on chloroplast DNA of matK gene. This research uses a descriptive method with a laboratory experiment. Total DNA was obtained by leaf tissue extraction and purification. The matK gene was amplified using the PCR method and visualized with automatic electrophoresis, sequencing was performed at FIRST BASE Singapore. The result of the analysis of the gene sequence of North Min Minerals using Barcode Of Life Database (BOLD) Systems shows that Pala Wori and Pala Patokaan have 99% similarity with Myristica maingayi and Myristica glubosa. While the reconstruction of the phylogeny tree shows the North Minahasa Pala has the closest resemblance to Myristica fatua.